Possible association between lipid profile and uterine fibroid size - Turkey, Banan Natiq; Rubayae, Bushra J. Al. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Uterine fibroid is the most common benign tumor in reproductive age group, arising from single smooth muscle cell of the uterus. Steroid hormones, estrogen, and progesterone are considered to be the most important links in the pathophysiology of uterine fibroid; meanwhile estrogens influence several aspects of lipid metabolism; so it's possible to theorize a relationship between uterine fibroid size and dyslipidemia. Aim of the study was to evaluate possible association of lipid profile with uterine fibroid size. Methods: This was a cross sectional study performed in Babylon Teaching Hospital for Maternity and Pediatrics during the period from 1st of March 2020- 1st of December 2020. This study included one hundred women diagnosed with uterine fibroid using abdominal and/or transvaginal ultrasound, fifty patients with large uterine fibroids ≥5cm3, and fifty patients with small uterine fibroid<5cm3. Serum lipid profile was measured in both groups in fasting state for comparison. Results: The most common complaint was abnormal uterine bleeding in both groups. body mass index were 20-29.9; and significant difference between group1 that showed a lower levels of high-density lipoprotein 40.82±9.4, higher levels of low-density lipoprotein 94.79±35.07 and total serum cholesterol 155.7±43.63 and group 2 that showed higher level of high density lipoprotein 50.7±6.55, lower level of low density lipoprotein 51.49±15.2 and total cholesterol 123.2±14.18 with p value <0.001.while non-significant difference between the two groups in term of very low density lipoprotein with p value 0.878 and triglyceride with p value 0.879. Conclusions: Dyslipidemia in the form of low high density lipoprotein, high low density lipoprotein and high cholesterol was significantly associated with increased size of uterine fibroid.